FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Jaladri, Engson Qinaris; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to test empirically the influence of human research quality, internal control system, facilities and infrastructures, and organization commitment to the effectiveness of the implementation of accrual based government accounting standard. This research is used qualitative approach. The sample collection method has been done purposive sampling. The data is primary data which has been obtained by issuing questionnaires. The data analysis technique has been carried out by using multiple liniear regressions. The result of this research shows that human resources do not have any influence to effectiveness of the implementation of accrual based government accounting standard. Meanwhile, internal control system, facilities and infrastuctures, and organization commitment has positive influence to the effectiveness of the implementation of accrual based government accounting standard.Keywords: Accrual based government accounting standard, human resources quality, internal control system, facilities and infrastuctures, organization commitment